Impact of distance learning on the health of students at pedagogical universities - Zakorkina Natalya Arkadyevna; Kurdumanova Olga Ivanovna; Zharkikh Larisa Aleksandrovna; Gilyazova Irina Borisovna (SHS Web of Conferences, 2021)
In recent years, the problem of deteriorating health of students studying in a distance format has been very urgent. On the one hand, the volume of the teaching load, including interesting educational programs in the online format, is increasing; on the other hand, there are no sanitary rules governing the requirements for the educational process in universities. The research purpose is to establish the features of health disorders of distance learning students. A survey was conducted among full-time and distance learning students. Through the analysis of variance, the strength of the impact of each factor related to deviations in students’ health was determined. Statistical reliability was confirmed using variance and special tables. The conducted research identified informatively significant factors related to health deviations of distance learning students. The analysis of variance was used to assess the influence of factors and their strength. Reliability of the impact of factors was determined using variance and special tables. The results are reliable (p<0.001). The available literary sources do not cover the problem of ranking the leading factors. Among them, a decrease in physical activity, emerging sub-health forms, visual impairments, changes in the general psychoemotional state are of particular importance. The following conclusions can be done. The revealed features of health disorders in distance learning students are associated with a decrease in physical activity, the development of hypodynamia, emerging sub-health states, visual impairment, a change in the general psychoemotional state. The distance learning process shall be regulated by Sanitary Rules and Regulations developed for universities.